Pengelolaan Wakaf Tunai Pada Badan Wakaf Indonesia (BWI) Kota Binjai - Elfara Annesca; Marliyah Marliyah; Kamila Kamila (LPPM Universitas Labuhanbatu, 2025)
This study aims to determine the management of money Waqf with SWOT approach strengths, weaknesses, opportunities and threats, after which it will be seen what strategies will be taken to maximize the strengths and opportunities, as well as minimize the weaknesses and threats that come. This study uses a descriptive-qualitative approach, that is to explain, describe, and describe what is, then analyze and draw conclusions. Data collection techniques used by researchers are observation, interviews and documentation. The study began by giving general questions to informants, namely the chairman and Secretary of the BWI implementing agency in Binjai City. The results of this study concluded that the management of the Indonesian Waqf Board (BWI) Binjai city is still limited, BWI Binjai city has not been able to do much regarding cash Waqf but is still in the process of collection. The strategy that can be done is to socialize to the public about the concept of Waqf money. The results of the study with SWOT analysis showed IFAS score of 1.92 strengths and 1.25 weaknesses, and EFAS score of 1.82 opportunities and 1.07 threats. So the most appropriate strategy in managing money Waqf in BWI Binjai City is a strategy that utilizes internal strength and utilizes external opportunities.